Effect of the spin-orbit interaction on partial entangled quantum network - Abdel-Aty, A.-H. (Springer Verlag, 2014)
Dzyaloshiniskii-Moriya (DM) interaction is used to generate entangled network from partially entangled states in the presence of the spin-orbit coupling. The effect of the spin coupling on the entanglement between any two nodes of the network is investigated. It is shown that the entanglement decays as the coupling increases. For larger values of the spin coupling, the entanglement oscillates between upper and lower bounds. For initially entangled channels, the upper bound does not exceed its initial value, whereas for the channels generated via indirect interaction, the entanglement reaches its maximum value. Â© Springer Science+Business Media Singapore 2014.